Hacking for dummies - Beaver, Kevin (Wiley Pub., 2007)
Shows network administrators and security testers how to enter the mindset of a malicious hacker and perform penetration testing on their own networks Thoroughly updated with more than 30 percent new content, including coverage of Windows XP SP2 and Vista, a rundown of new security threats, expanded discussions of rootkits and denial of service (DoS) exploits, new chapters on file and database vulnerabilities and Google hacks, and guidance on new hacker tools such as Metaspoilt Topics covered include developing an ethical hacking plan, counteracting typical hack attacks, reporting vulnerabili.
Includes bibliographical references and index. - Print version record
Keywords: Computer security; Computer networks -- Security measures; Hackers; Sécurité informatique; Réseaux d'ordinateurs; Sécurité; Mesures; Pirates informatiques; COMPUTERS; Internet; Security; COMPUTERS; Networking; Security; COMPUTERS; Security; General; Computer networks; Security measures; Computer hackers; Engineering & Applied Sciences; Computer Science